Iran Economic Monitor, Spring 2017 : Oil-Driven Recovery - World Bank (Washington, DC, 2017)
The Iran Economic Monitor provides an update on key economic developments and policies over the past six months. It examines these economic developments and policies in a longer-term and global context, and assesses their implications for the outlook for the country. Its coverage has ranged from the macroeconomy to financial markets to indicators of human welfare and development. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged in Iran.